Sexual Violence and Women’s Education: Examining Academic Performance and Persistence - Stermac, Lana; Cripps, Jenna; Amiri, Touraj; Badali, Veronica (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Sexual violence continues to be a serious problem on university campuses. While the negative psychological and health effects of sexual violence are well known, it is only recently that attention has focused on how these behaviours impact education, particularly women’s education. This study contributes to this area and examined the impact of types of sexual violence on behavioural and attitudinal indicators of academic performance and persistence among students reporting sexual violence. Undergraduate women attending university in Ontario, Canada (N= 934) responded to survey measures of academic performance, attitudes towards education and sexual violence experiences. The results indicate that sexual violence has a deleterious impact on women’s academic performance including and beyond grades. Women students who experienced sexual violence reported more delays and failures on assignments, courses and exams, were more likely to endorse attendance problems and thoughts of dropping out or quitting than students not reporting sexual violence. Type of sexual violence experienced was also related to academic performance.  The results are discussed in terms of the need to understand components of academic performance as well as factors that may contribute to outcomes for students. Findings have implications for intervention and policy development.